Measuring Device and Material ZT in a Thin-Film Si-Based Thermoelectric Microgenerator - Pablo Ferrando-Villalba; Antonio Pablo Pérez-Marín; Llibertat Abad; Gustavo Gonçalves Dalkiranis; Aitor F. Lopeandia; Gemma Garcia; Javier Rodriguez-Viejo (Nanomaterials, 2019)
Thermoelectricity (TE) is proving to be a promising way to harvest energy for small applications and to produce a new range of thermal sensors. Recently, several thermoelectric generators (TEGs) based on nanomaterials have been developed, outperforming the efficiencies of many previous bulk generators. Here, we presented the thermoelectric characterization at different temperatures (from 50 to 350 K) of the Si thin-film based on Phosphorous (n) and Boron (p) doped thermocouples that conform to a planar micro TEG. The thermocouples were defined through selective doping by ion implantation, using boron and phosphorous, on a 100 nm thin Si film. The thermal conductivity, the Seebeck coefficient, and the electrical resistivity of each Si thermocouple was experimentally determined using the in-built heater/sensor probes and the resulting values were refined with the aid of finite element modeling (FEM). The results showed a thermoelectric figure of merit for the Si thin films of <semantics> z T </semantics> = 0.0093, at room temperature, which was about 12% higher than the bulk Si. In addition, we tested the thermoelectric performance of the TEG by measuring its own figure of merit, yielding a result of ZT = 0.0046 at room temperature.